Application of the Humanistic Paradigm in Social Service Against People with Mental Disorders (PWMD) - Hermawan, Hermawan (Universitas Padjadjaran, 2025)
This study aims to analyze the application of the humanistic paradigm in social rehabilitation services for People with Mental Disorders (PWMD) and to evaluate its impact on service quality and client independence. The research applied a qualitative case study design at the Malang City Social Services Department, with data collected through observation, in-depth interviews, and document analysis. Respondents included social workers, patients, and family members. The findings reveal that the humanistic paradigm—emphasizing respect, dignity, emotional well-being, empathy, and individuality—has been effective in improving service quality and fostering client independence. This approach is more responsive to the needs of clients and families by prioritizing human dignity, empowerment, empathetic relationships, and a supportive recovery environment. The implications highlight the need for policy development and institutional support that integrate humanistic theory into social rehabilitation practices. The study contributes novelty by showing that the humanistic approach offers high value in creating humane and quality services, an area still underexplored in Indonesian social service practice.